Pedro Salinas’ science-fiction novel: generic resources - Moreno Serrano, Fernando Angel (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
An analysis about Pedro Salinas’ La bomba increíble: una fabulación is interesting because we can enjoy it from different points of view. In the first place, it has not been studied as the rest of his literary texts, although the values of this little masterpiece deserve a special attention that has not taken place. On the other hand, it is a strange case of the science fiction novels in Spanish literature written by a Spanish canonic author. Finally, it is amazing how the poet showed all his obsessions, fears and poetic visions with a novel with the future as its main subject. An analysis of the mechanisms of construction used by Salinas –specially the fictional ones, but also the linguistic and symbolic ones– will allow us to understand the novel and consequently enjoy it more. Thus we will be able to put it in the place where it should be.